Teaching secondary mathematics - Rock, David; Brumbaugh, Douglas K.; Brady, Thomas J. P. (New York, NY : Routledge, 2024)
"Solidly grounded in up-to-date research, theory and technology, Teaching Secondary Mathematics is a practical, student-friendly, and popular text for secondary mathematics methods courses. It provides clear and useful approaches for mathematics teachers, and shows how concepts typically found in a secondary mathematics curriculum can be taught in a positive and encouraging way. The thoroughly revised fifth edition combines this pragmatic approach with truly innovative and integrated technology content throughout. Synthesized content between the book and a comprehensive Instructor and Student Resource website offers expanded discussion of chapter topics, additional examples, and technological tips, such as using and assessing Artificial Intelligence. Each chapter features tried-and-tested pedagogical techniques, problem-solving challenges, discussion points, activities, mathematical challenges, and student-life-based applications that will encourage students to think and do. New to the fifth edition: A fully revised chapter on technological advancements in the teaching of mathematics, including the use of Artificial Intelligence A new chapter on equity, shame, and anxiety in the mathematics classroom Connections to both the updated NCTM Focal Points and Standards Problem-solving challenges and sticky questions featured in each chapter to encourage students to think through everyday issues and possible solutions A fresh interior design to better highlight pedagogical elements and key features A completely updated Instructor and Student Resource site with chapter-by-chapter video lessons, teacher tools, problem solving Q&As, exercises, and helpful links and resources"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Secondary).